Reactive Astrocytes in Neurodegenerative Diseases - Li, Kunyu (Aging Dis, 2019)
Astrocytes, the largest and most numerous glial cells in the central nervous system (CNS), play a variety of important roles in regulating homeostasis, increasing synaptic plasticity and providing neuroprotection, thus helping to maintain normal brain function. At the same time, astrocytes can participate in the inflammatory response and play a key role in the progression of neurodegenerative diseases. Reactive astrocytes are strongly induced by numerous pathological conditions in the CNS. Astrocyte reactivity is initially characterized by hypertrophy of soma and processes, triggered by different molecules. Recent studies have demonstrated that neuroinflammation and ischemia can elicit two different types of reactive astrocytes, termed A1s and A2s. However, in the case of astrocyte reactivity in different neurodegenerative diseases, the recently published research issues remain a high level of conflict and controversy. So far, we still know very little about whether and how the function or reactivity of astrocytes changes in the progression of different neurodegenerative diseases. In this review, we aimed to briefly discuss recent studies highlighting the complex contribution of astrocytes in the process of various neurodegenerative diseases, which may provide us with new prospects for the development of an excellent therapeutic target for neurodegenerative diseases.